Manipulation of the cervical spine—a pilot study - Howe, D. H. (1983)
A randomized controlled trial of manipulation of the cervial spine was carried out on 52 patients in general practice, and the results were assessed symptomatically and goniometrically for three weeks. Manipulation produced a significant immediate improvement in symptoms in those with pain or stiffness in the neck, and pain/paraesthesia in the shoulder, and a nearly significant improvement in those with pain/paraesthesia in the arm/hand. Manipulation also produced a significant increase in measured rotation that was maintained for three weeks and an immediate improvement in lateral flexion that was not maintained. This is to our knowledge the first published formal trial of such manipulation and should increase interest in this form of treatment by the medical profession.